Development of Hologram-Based Learning Media for Class VII Science Subjects at SMP Negeri 53 Makassar - Fauzan, M Agung; Syamsurijal, Syamsurijal; Mappeasse, Muh Yusuf (Edumaspul: Jurnal Pendidikan, 2022)
Abstract - This study aims to (a) find out the results of the feasibility test of hologram-based learning media in science subjects class VII SMP Negeri 53 Makassar, (b) find out the results of users’ responses to hologram-based learning media in science subjects class VII SMP Negeri 53 Makassar, (c) find out the results of the effectiveness and practicality of hologram-based learning media in class VII Science subjects at SMP Negeri 53 Makassar. This research is research and development (Research and Development) with the ADDIE development model consisting of analysis, design, development, implementation, and evaluation. Based on the results of the research, the feasibility test of hologram-based learning media is based on the assessment of media experts in the very feasible category and the material expert’s assessment in the very feasible category, so that this media meets the very feasible category to be used as a learning medium. The responses of class VII students of SMP Negeri 53 Makassar as media users based on the results of the small group trials and the results of the large group trials were in very good categories, so that the media was feasible to be used as learning media in the learning process. And the developed hologram-based learning media meets effective and practical aspects. It is known that based on the average score and classical completeness posttest higher than the average score and classical completeness pretest, so that the developed media is effective. Meanwhile, based on small group trials and large group trials, the media received a positive response in the "Very Good" category, so that it can be said that the developed media provides useful value and convenience for users, in other words, hologram-based media is practical to use. Kata kunci: Media Pembelajaran, Hologram, ADDIE